2007
DOI: 10.1016/j.ijsolstr.2007.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-plane deformation measurements of an aluminium plate during quasi-static perforation using structured light and close-range photogrammetry

Abstract: An optical system using structured light and close-range photogrammetry for full-field continuous measurements of the out-of-plane deformation of a metal plate loaded at its centre by a moving punch is presented. The system is applicable both for quasi-static and dynamic loading conditions, but in this paper focus will be on the former. In the tests, a square AA5083-H116 aluminium plate is mounted in a circular frame and penetrated from above by a cylindrical punch, while the out-of-plane deformation is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…This fact could suggest the use of photogrammetry and multi-camera systems for contouring out-of-plane displacements (see, for instance, Grytten et al, 2007). The error made on the out-of-plane displacement value for a given point P of the deformed surface corresponds to the error made on a spatial coordinate equal to the distance between P and the reference plane.…”
Section: Discussionmentioning
confidence: 99%
“…This fact could suggest the use of photogrammetry and multi-camera systems for contouring out-of-plane displacements (see, for instance, Grytten et al, 2007). The error made on the out-of-plane displacement value for a given point P of the deformed surface corresponds to the error made on a spatial coordinate equal to the distance between P and the reference plane.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that the boundary behaves somewhere between fixed and simply supported, and that the effect of the boundaries increases as the impact velocity decreases [46]. In other words, as we approach quasi-static loading, more of the plate will be affected.…”
Section: Parametric Studymentioning
confidence: 99%
“…Although the several applications of photogrammetric measurements are currently in use and demonstrated to provide very accurate measurements for a wide variety of disciplines, its use is usually limited to small measurement volumes and experiments that are performed in laboratories or similar controllable environments. Within this small measurement volume it can be efficiently used for different purposes such as; -3D shape determination, modeling and reverse engineering (4), (5), (6) -Static or dynamic deformation measurements (7), (8), (9), (10), (11), (12), (13) , (14), (15) -Modal analysis and system identification (16), (17), (18), (19), (20), (21) This technology was for the first time applied on a MW scale wind turbine within the scope of this work. The 3D dynamic response of the rotor was captured at 33 different locations simultaneously by using 4 CCD (charge coupled device) cameras while the turbine was rotating.…”
Section: Measurement Systemsmentioning
confidence: 99%